Insights, beliefs, and myths surrounding tuberculosis among pulmonary patients with delayed healthcare access in a high-burden TB state in Nigeria – a qualitative inquiry - Adeoye, Beatrice Damilola; Michael, Turnwait Otu; Agbana, Richard Dele (Frontiers in Sociology, 2024)
Nigeria grapples with a substantial burden of tuberculosis (TB), particularly in Oyo State, designated as a high-burden State for TB. Effectively addressing this persistent health challenge necessitates more than just medical interventions; it requires a profound understanding of the diverse insights, beliefs, and myths held by TB patients. This qualitative study explores the perspectives of pulmonary TB patients with delayed healthcare access in Oyo State, Nigeria, focusing on their beliefs, and conceptions. In-depth interviews were conducted with 25 TB patients and 20 healthcare providers. Thematic analysis of patients' responses revealed a complex interplay between cultural, spiritual, and biomedical insights. These challenges questioned the germ theory, associating TB with witchcraft and spiritual attacks. Beliefs in hereditary transmission, links between tobacco use and health outcomes, and uncertainties about infection nature underscored disparities influenced by socio-economic factors. Insights into transmission ideas, preventive measures, and treatment beliefs highlighted a blend of culturally influenced and scientifically supported strategies. Healthcare providers' insights emphasized the necessity for targeted health education. These findings contribute to a nuanced understanding of TB perceptions, emphasizing the importance of culturally sensitive interventions to enhance awareness and promote timely and accurate health-seeking behaviors.